2021
DOI: 10.1021/acsinfecdis.1c00003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis Uncovers Transient Ceftazidime Tolerance in Burkholderia Biofilms

Abstract: Burkholderia pseudomallei is an etiological agent of melioidosis, a severe community-acquired infectious disease. B. pseudomallei strain K96243 is sensitive to the drug ceftazidime (CAZ), but has been shown to exhibit transient CAZ tolerance when in a biofilm form. To investigate an observed shift in gene expression profile during CAZ tolerance condition and to better understand the mechanistic aspects of this transient tolerance, RNA-sequencing was performed on B. pseudomallei K96243 from the following three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…In contrast to their planktonic counterparts, bacteria within the biofilm can express specific genes that enhance bacteria tolerance [11]. For instance, Burkholderia pseudomallei, responsible for melioidosis, has been reported to tolerance to ceftazidime (CAZ) in its biofilm state, while remaining sensitive in its planktonic state [100]. RNA-sequencing studies of this bacterium across planktonic, biofilm, and planktonic shedding states revealed that approximately 10% of gene expression changed in both biofilm and planktonic shedding compared to planktonic bacteria.…”
Section: Specific Gene Expressionmentioning
confidence: 99%
“…In contrast to their planktonic counterparts, bacteria within the biofilm can express specific genes that enhance bacteria tolerance [11]. For instance, Burkholderia pseudomallei, responsible for melioidosis, has been reported to tolerance to ceftazidime (CAZ) in its biofilm state, while remaining sensitive in its planktonic state [100]. RNA-sequencing studies of this bacterium across planktonic, biofilm, and planktonic shedding states revealed that approximately 10% of gene expression changed in both biofilm and planktonic shedding compared to planktonic bacteria.…”
Section: Specific Gene Expressionmentioning
confidence: 99%
“…A variety of aerobes can degrade PCBs, but Paraburkholderia xenovorans strain LB400 demonstrates higher degradation efficacy for wide ranges of PCBs (mono- to hexa-chlorinated biphenyls). , PCB oxidation proceeds via the bph pathway; thus, bphA is commonly used as a biomarker because it encodes biphenyl dioxygenase, the initial catabolic enzyme in the pathway. ,, Specific carbon/energy sources (e.g., biphenyl, benzoate) are required for bph pathway induction, and many PCB congeners with 6 chlorines or less are cometabolized in the presence of biphenyl or benzoate. , Bioaugmenting sediments with suspended LB400 cells can efficiently oxidize LC-PCB congeners (up to trichlorinated homologues) and mitigate flux to the air. , Nevertheless, free cells often demonstrate unsatisfactory survivability and activity due to environmental fluctuations and nutrient availability factors that can be moderated when cells exist as biofilms. Biofilms display increased gene expression levels and produce exopolysaccharides that improve stress tolerance and cell removal resistance. , Multiple studies have examined immobilized anaerobes that dechlorinate PCBs, , but comparatively few have focused on removing LC-PCBs through bioaugmentation of immobilized PCB-degrading aerobes to mitigate the direct human exposure pathway. Improved LC-PCB bioremediation strategies require an enhanced understanding of immobilized PCB-degrading cells and how cells interact with surface materials.…”
Section: Introductionmentioning
confidence: 99%